THU0263 Analysis on characteristics of 82 patients with ankylosing spondylitisin japan. (12th June 2018) - Tada, K.; Kobayashi, S.; Hayashi, E.; Ogasawara, M.; Inoue, H.; Yamaji, K.; Tamura, N.
Abstract : Background: Ankylosing spondylitis (AS) is the prototype of spondyloarthritis, which affects sacroiliac joints, spine, peripheral joints and enthuses. HLA-B27 is known to be related with AS and there is a considerable number of patients suffering from AS among other rheumatic diseases. In Japan, however, the prevalence of AS was reported to be less than 0.1% much lower than western countries and also other East Asian countries 1) 2) 3) . This is due to the low frequency of HLA-B27 in Japanese (0.3%) compared to 5%–10% in the countries mentioned above. Because of small number of AS patients, clinical features and HLA-B27 positivity has not been well investigated in Japanese patients with AS. Since our hospital has an outpatient specialising in AS and there are many patients, we conducted a survey on AS Objectives: In this study, we examined the characteristics of patients with AS in our hospital and compared the data of patients with AS in Japan and overseas. Methods: We conducted a questionnaire survey on patients fulfilling the modified New York criteria for AS. A questionnaire included demographic data and histories. We also retrospectively investigated the data of blood test, radiographs and the presence of inflammatory back pain (IBP), HLA-B27, enthesitis, dactylitis, radiographic sacroiliitis and extra-articular manifestation. Results: A total of 82 patients (82.9% male) including Japanese (68), Chinese, 9 Korean 5 with AS who fulfilled the modified New York criteria were enrolled from May in 2013 to April in 2016. Of 68 patients with HLA-B27 test result, 61 patients (89.7%) were HLA-B27 positive. Of 54 Japanese patients, 48 patients (88.9%) were HLA-B27 positive. IBP, enthesitis, dactylitis, bamboo spine and uveitis were found in 67 patients (81.7%), 31 patients (37.8%), 5 patients (6.1%), 44 patients (53.7%) and 30 patients (36.6%), respectively. Conclusions: In Japanese AS patients, the prevalence of HLA-B27 was high (almost 90%) and other characteristics were similar with those of Western countries. In Japan where the frequency of HLA-B27 is very low, B27 positivity is considered to have high diagnostic value. References: [1] Hukuda S, Minami M, Saito T, Spondyloarthropathies in Japan; Nationwide questionnaire survey performed by the japan ankylosing spondylitis society. J Rheumatol2001;28: 554–559. [2] Calin A, Fries JF. Striking prevalence of ankylosing spondylitis in "healthy" W27 positive males and gemales. N Engl J Med. 1975;293:835–839. [3] Akkoc N, Khan MA. Overestimation of the prevalence of ankylosing spondylitis in the Berlin study: comment on the article by Braun, et al. Arthritis Rheum2005;52–4048–4049. Disclosure of Interest: None declared